Hand model of the brain training as emotion regulation method for elementary school students - Lita Patricia Lunanta; Reneta Kristiani; Aurelia Ardani (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
In the era of the COVID-19 pandemic, learning from home comes with positive and negative consequences. The sense of security that children get from distance learning brings negative consequences where children need to adjust to a new paradigm. Problems around learning from home included mental health and emotional problems for students. This psychoeducation aimed to explain the emotion regulation process and how the brain worked in emotion processing. We conducted the program with a pre-survey and interviews with teachers and school principals. Furthermore, online mentoring and surveys to students accompanied by their parents. It is hoped that students could understand their emotions and the basic steps to regulate. The hand model of the brain is the model of the brain in hands to explain concretely the hierarchy and connection between different parts of the brain concerning emotions. This program got a positive response from the participants. Psychoeducation results show an increase in understanding and gave positive feedback that this program is effective and fit to what they needed.